Estimating the optimal efflux inhibitor concentration of carvacrol as a function of the bacterial physiological state - Jánosity, Anna; Baranyi, József; Surányi, Botond Bendegúz; Možina, Sonja Smole; Taczman-Brückner, Andrea; Kiskó, Gabriella; Klančnik, Anja (Frontiers in Microbiology, 2023)
Our aim was to find the optimal efflux inhibitor concentration of a natural component, carvacrol, as a function of the physiological state of Escherichia coli. Using fluorescence-based measurements with two strains of E. coli, the effect of carvacrol was assessed at 17 sub-inhibitory concentrations, at which the bacterial efflux mechanism was compromised. The efficacy of carvacrol, as an efflux inhibitor, was compared to synthetic inhibitors and we found carvacrol the most efficient one. We considered the accumulation of Ethidium Bromide (EtBr) as a proxy for drugs spreading in the cell, thus measuring the efflux activity indirectly. The change in membrane integrity caused by the exposure to carvacrol was monitored using the LIVE/DEAD BacLight Bacterial Viability kit. To find the optimal inhibitory concentration of carvacrol, we used predictive microbiology methods. This optimum varied with the bacterial physiological state, as non-growing cultures were less susceptible to the effect of carvacrol than growing cultures were. Moreover, we point out, for the first time, that the efflux-mediated resistance of untreated cultures was also stronger in the non-growing than in the growing phase at population level.